2007
DOI: 10.3748/wjg.v13.i39.5282
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde jejunoduodenogastric intussusception due to a replacement percutaneous gastrostomy tube presenting as upper gastrointestinal bleeding

Abstract: Percutaneous endoscopic gastrostomy (PEG) tube complications can be serious or life threatening. Retrograde intussusception is a very rare complication of PEG tubes with only 9 cases reported in the literature. We describe a case of retrograde intussusception, associated with the use of a Foley catheter as a replacement gastrostomy tube, presenting with upper gastrointestinal bleeding. To our knowledge, this is the first reported case of PEG-related retrograde intussusception successfully managed in a non-surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…However, further review of the literature revealed several case studies detailing a number of unique complications arising from the use of Foley catheter in place of dedicated gastrostomy feeding tube 9–15. The common theme of the described complications is the distal migration of the Foley catheter balloon postpyloric into the small bowel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further review of the literature revealed several case studies detailing a number of unique complications arising from the use of Foley catheter in place of dedicated gastrostomy feeding tube 9–15. The common theme of the described complications is the distal migration of the Foley catheter balloon postpyloric into the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Date et al reported the Foley balloon lodging in the pyloric channel, causing gastric outlet obstruction and a prepyloric ulcer 9. Once the balloon migrates past the pylorus, a number of complications including duodenal obstruction, duodenal ischaemia, upper GI bleeding, duodenojejunal intussusception and even obstructive jaundice have been described 11–14. Travelling further in the small bowel, the Foley balloon can again cause obstruction as described by Pereira and Mersich, who used percutaneous balloon aspiration as a minimally invasive method for relieving the obstruction 15…”
Section: Discussionmentioning
confidence: 99%
“…JGI is defined as the prolapse of an anastomosed jejunum into the stomach (retrograde intussusception; Ibegbu et al, 2007). Since 1914, only 200 cases of JGIs have been reported in the literature (Samarasam et al, 2005;Miah et al, 2006).…”
Section: Classifications and Terminologymentioning
confidence: 99%
“…Antibiotic prophylaxis is not necessary in patients already receiving appropriate broad-spectrum antibiotics around the time of the procedure, to lower the risk of Methicillin-Resistant Staphylococcus aureus (MRSA), which is commonly found in infected PEG sites (15,72). Some studies found beneficial results in pre-screening for MRSA (73,74).…”
Section: Infectionmentioning
confidence: 99%